2000
DOI: 10.1007/s001270050270
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal acts and ideation in homosexual and bisexual young people: a study of prevalence and risk factors

Abstract: The identified increased risk of suicidal ideation among homosexual or bisexual young people is associated with depression and may lead to suicidal behaviour, independent of sexual orientation, especially in the presence of a role model of suicidal behaviour, and among those with unsatisfying friendships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
63
0
3

Year Published

2002
2002
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(67 citation statements)
references
References 0 publications
1
63
0
3
Order By: Relevance
“…Young people with high levels of hopelessness tend to perceive their social support as low (Biggam & Power, 1997). Research that has been conducted with lesbian, gay and bisexual youth has consistently found a markedly higher risk of suicidal thoughts and behaviours among these groups than among heterosexual youth (Bagley & Tremblay, 1997;D'Augelli & Hershberger, 1993;Hershberger & D'Augelli, 1995;Remafedi, French, & Story, 1998;Rotheram-Borus, Hunter, & Rosario, 1994;van Heeringen & Vincke, 2000). The above studies clearly document the relationship between self-esteem, hopelessness and depression as indicators of mental wellbeing and social support.…”
Section: Mental Wellbeing and Lesbian And Gay Youthmentioning
confidence: 69%
“…Young people with high levels of hopelessness tend to perceive their social support as low (Biggam & Power, 1997). Research that has been conducted with lesbian, gay and bisexual youth has consistently found a markedly higher risk of suicidal thoughts and behaviours among these groups than among heterosexual youth (Bagley & Tremblay, 1997;D'Augelli & Hershberger, 1993;Hershberger & D'Augelli, 1995;Remafedi, French, & Story, 1998;Rotheram-Borus, Hunter, & Rosario, 1994;van Heeringen & Vincke, 2000). The above studies clearly document the relationship between self-esteem, hopelessness and depression as indicators of mental wellbeing and social support.…”
Section: Mental Wellbeing and Lesbian And Gay Youthmentioning
confidence: 69%
“…Other studies have also shown this association among men (Remafedi, 1999;Remafedi et al, 1998;Skegg, Nada-Raja, Dickson, Paul, & Williams, 2003), although one study only found homosexual young women, and not homosexual young men, more at risk for suicide attempt (Van Heeringen & Vincke, 2000).…”
Section: Comparison With Other Studiesmentioning
confidence: 95%
“…Studies with convenience samples of young gay men (between 15e16 and 24e27 years) in western Europe have yielded lifetime prevalences of 71% for suicidal ideation (McNamee, 2006) and 12e27% for suicide attempts (van Heeringen and Vincke, 2000;Cochand et al, 2000;Hanner, 2002;McNamee, 2006;Hegna and Wichstrøm, 2007). Using convenience samples of gay men in French-speaking Switzerland, Cochand and colleagues have reported lifetime prevalences of 23% for suicide attempts among gay men (Cochand and Bovet, 1998) and 24% among young gay men aged 16e25 years (Cochand et al, 2000).…”
Section: Prevalence Of Suicidality Among Gay Menmentioning
confidence: 99%